(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The article examines the professional competencies of a modern manager, higher education training, and the analysis of employers’ requirements. The main competencies of vocational education – social, communicative, informational, specialized, and cognitive – are closely linked to work culture and managerial activities. Research findings indicate that innovative thinking, responsibility, teamwork, and decision-making skills are the most important qualities for an effective manager.